PENGARUH KESEHATAN BANK TERHADAP RETURN SAHAM - Dian Fordian (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2018)
This research aims to know and study the influence of bank health is represented by the variable Capital Adequacy Ratio (CAR), the Non-Performing Loan (NPL), and Loan To Deposit Ratio (LDR) towards the stock return bank State-Owned Enterprises which listings in Indonesia stock exchange (IDX). The data used are secondary data in the form of annual data from the year 2013-2017. The dependent variables used stock return as for its independent variable is the variable CAR, NPL, and LDR. Data analysis using multiple regression in panel data (fixed effect model). The results of this research show that there is a significant influence of the simultaneous independent variables the dependent variables against. While partially only variables that influence the NPL negative and significantly to the stock return, while variable CAR and LDR have no effect against the stock return bank State-Owned Enterprises listed at the IDX.